Optimise behavioural health and human factors research for deep space missions by classifying analogue scenarios and fidelity - Károly Kornél Schlosser; Károly Kornél Schlosser; Károly Kornél Schlosser; Károly Kornél Schlosser; Ilaria Cinelli; Ilaria Cinelli; Thorsten Waelde; Thorsten Waelde; Luis Luque Álvarez; Gábor Pokorádi; Krisztián Pósch; Iya Whiteley (Frontiers in Space Technologies)
Future human space missions beyond low Earth orbit face significant challenges in understanding and managing astronaut behaviour and performance in extreme environments, with behavioural health remaining a critical knowledge gap. Ground research in analogue environments offers cost-effective means to address these challenges. Still, due to analogues' compromised fidelity levels, the findings derived from such activity may only sometimes be reliable, rigorous and transferable to human space exploration. We hypothesise that gaps in understanding human behaviour and performance could be significantly addressed by using analogues with higher realism, which can accurately replicate specific conditions and yield more relevant insights to better inform future space missions. This paper takes a behavioural health approach to future spaceflight and evaluates analogue scenarios in such a perspective, to ensure the ecological validity and reliability of behavioural health research outcomes. Furthermore, we emphasise the functional-contextual importance of the features of analogue scenarios to resemble the complexity of current and/or future human space mission scenarios in terrestrial settings. Building on previously published research, we introduce the Extended Feature Classification System of Analogues (EFCSA) to identify analogue scenarios with greater realism. It evaluates the analogue’s fidelity level based on contextual and human factor features. Features themes include isolation, lack of resupplies, element of exploration, environmental conditions, biopsychosocial impact, and skill expertise, among others. Based on the EFCSA, we preliminarily identified a range of analogue scenarios into Low-, Mid-, and High-fidelities and introduced the term “Peak-fidelity”. The latter (such as wet cave exploration, and submerged cave system exploration and camping) and high-fidelity scenarios (saturation diving/underwater habitats, polar expeditions, polar overwintering, and submarines) offer the greatest fidelity in replicating space features with further potential. Mid-fidelity activities include technical diving (open water/pools) and dry cave exploration and camping. Low-fidelity activities include recreational diving (open water, <40 m), marine expeditions and sailing, piloting, parabolic flight, desert-based surface analogues and mountaineering expeditions. It is important to highlight that these results do not diminish the utility of other analogues; instead, the EFCSA helps to identify specific purposes for which analogues are useful, and serves as a means to improve analogue realism.